Automated Technology for Verification and Analysis
DOI: 10.1007/978-3-540-75596-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Mechanizing the Powerset Construction for Restricted Classes of ω-Automata

Abstract: Abstract. Automata over infinite words provide a powerful framework to solve various decision problems. However, the mechanized reasoning with restricted classes of automata over infinite words is often simpler and more efficient. For instance, weak deterministic Büchi automata (wdbas) can be handled algorithmically almost as efficient as deterministic automata over finite words. In this paper, we show how and when the standard powerset construction for automata over finite words can be used to determinize aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…For instance 40 formulae out of the 55 formulae from Dwyer et al (1998) are obligations. Dax et al (2007) did a comparison of the size produced by different translators (not Spot, which they did not know) with the size of the minimal WDBA. This revealed that although it was deterministic, the minimal WDBA usually had number states smaller or equal to that of the automata produced by the translators.…”
Section: Wdba Minimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance 40 formulae out of the 55 formulae from Dwyer et al (1998) are obligations. Dax et al (2007) did a comparison of the size produced by different translators (not Spot, which they did not know) with the size of the minimal WDBA. This revealed that although it was deterministic, the minimal WDBA usually had number states smaller or equal to that of the automata produced by the translators.…”
Section: Wdba Minimizationmentioning
confidence: 99%
“…Table 3 completes the benchmark of Dax et al (2007) using the sizes of the degeneralized automata generated by spot-0.7.1. The first column is the number of the formula, so you can compare with the figure for other tools displayed at http:// www.daxc.de/eth/atva07/index.html.…”
Section: Wdba Minimizationmentioning
confidence: 99%
“…5, the level reset alone is enough to replace transition ((1, 1), , (2, 1)) by transition ( (1, 1), , (2, 0)), therefore avoiding state (2, 1) and all its descendants. Using level caching without level reset, and assuming the descendants of (2, 0) have been built before those of (2, 1), then state (2, 1) would be connected to states (3, 0) and (4, 0) instead of states (3,1) and (4,1). It is hard to find a small example to illustrate that both optimizations are useful together: the smallest such occurrence in our benchmarks has 20 states.…”
Section: Scc-based Degeneralizationmentioning
confidence: 99%
“…Besides the techniques discussed in this paper, Spot implements the WDBA-minimization algorithm of Dax et al [4] that converts any TGBA representing an obligation property [14] into a minimal Weak Deterministic Büchi Automaton. The corresponding function WDBA minimize(T , ϕ) requires the formula ϕ represented by automaton T to check the validity of the minimized automaton.…”
Section: Translation Scenariosmentioning
confidence: 99%
“…For instance, weak and terminal automata can be reduced very efficiently with techniques such as WDBA minimization [10]. Also simulations reductions [24] will be more efficient on automata with less acceptance conditions.…”
Section: Decomposing the Property Automaton According To Its Sccs Strmentioning
confidence: 99%